The measurement and modelling of vapour-liquid equilibria in ternary systems containing polar, cross-associating, and associating compounds - Thompson, Andrew Cameron (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEng)--Stellenbosch University, 2020.